Optimization of network information air navigation facilities by the generalized criterion of efficiency - Харченко, В.П.; Бабейчук, Д.Г.; Слюняєв, О.С. (Proceedings of National Aviation University (archive), 2009)
The analysis of structure of the system is formulated in this article. The author offers the method of optimization of network of informative facilities. The generalized criterion of efficiency of the aeronavigation system is chosen for criterion of optimization.